2011
DOI: 10.1590/s0100-06832011000500030
|View full text |Cite
|
Sign up to set email alerts
|

Dejeto líquido bovino em plantio direto: perda de carbono e nitrogênio por escoamento superficial

Abstract: A utilização de dejetos de animais na produção agrícola é uma alternativa de disposição do resíduo gerado na atividade pecuária, porém se aplicado inadequadamente pode causar problemas ambientais. Nesse sentido, o objetivo geral deste trabalho foi avaliar as concentrações e perdas de C e N por escoamento superficial em quatro doses de dejeto líquido bovino (0, 60, 120, 180 m³ ha-1 ano-1) aplicado em Latossolo franco-argiloarenoso com 13 % de declividade, manejado em plantio direto com soja, aveia-preta, milho … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
2
0
4
Order By: Relevance
“…According to Owens et al (2000), high doses of N applied successively in crops result in excessive levels of N-NO 3 -leached in concentrations that may exceed the maximum threshold allowed by law for drinkable water, which corresponds to the possible contamination of water with N-NO 3 -with the dosage applied. In the case of fertilization with 100 m 3 ha -1 of LSM, 38% of nitrate levels in percolated water were higher than 10 mg L -1 [According to the WHO, levels above 10 mg L -1 are considerably pollutants, with risk of environmental contamination (USEPA, 2002)], while in the other treatments, only 1 and 3% were observed in mineral fertilizations and 25 m 3 ha -1 of LSM, respectively ( Figure 6) (Silva et al, 2011;Timofiecsyk et al, 2012), a fact that is also observed by Santos et al (2015) conducted in the same site of the present work.…”
Section: Resultsmentioning
confidence: 99%
“…According to Owens et al (2000), high doses of N applied successively in crops result in excessive levels of N-NO 3 -leached in concentrations that may exceed the maximum threshold allowed by law for drinkable water, which corresponds to the possible contamination of water with N-NO 3 -with the dosage applied. In the case of fertilization with 100 m 3 ha -1 of LSM, 38% of nitrate levels in percolated water were higher than 10 mg L -1 [According to the WHO, levels above 10 mg L -1 are considerably pollutants, with risk of environmental contamination (USEPA, 2002)], while in the other treatments, only 1 and 3% were observed in mineral fertilizations and 25 m 3 ha -1 of LSM, respectively ( Figure 6) (Silva et al, 2011;Timofiecsyk et al, 2012), a fact that is also observed by Santos et al (2015) conducted in the same site of the present work.…”
Section: Resultsmentioning
confidence: 99%
“…as time passed. For this reason, correct handling and dosage addition into soil must to be take into account, remembering that the cultivated crop is an essential parameter (Silveira et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, em estudo similar a este, porém em solo de textura franco-argilo-arenosa, Silveira et al (2011) observaram diferenças significativas; a aplicação de 120 m 3 ha -1 ano -1 reduziu em 20 e 89 % a concentração média ponderada e a perda de COT, respectivamente, em relação ao tratamento sem aplicação. Essa diferença de comportamento no CO entre os dois tipos de solo deve-se possivelmente ao efeito positivo nos atributos físicos do solo com a aplicação de dejeto no solo franco-argilo-arenoso (Mellek et al, 2010), diminuindo significativamente as perdas de solo e água e, consequentemente, de CO.…”
Section: Concentração Média Ponderada E Perda De Carbono Orgânico Totalunclassified
“…As concentrações médias ponderadas de N tanto na forma de NO 3 -como de NH 4 + (Figuras 1c,e) foram maiores com a aplicação de dejeto, atingindo valores máximos na maior dose (180 m 3 ha -1 ano -1 ), o que ilustra o potencial poluidor de resíduos orgânicos, principalmente os aplicados na superfície do solo, em áreas agrícolas sob PD (Smith et al, 2001;Allen & Mallarino, 2008;Silveira et al, 2011 (Brasil, 2004;Conama, 2005), observa-se que até a dose de 120 m 3 ha -1 ano -1 a concentração média ponderada de NO 3 -, na água do escoamento superficial, está abaixo do limite máximo permitido por legislação; no entanto, a dose máxima de dejeto líquido bovino ultrapassou em 36,4 % este limite. Apesar dos baixos R. Bras.…”
Section: Concentração Média Ponderada E Perdas De N-no 3 -E N-nh 4 +unclassified
See 1 more Smart Citation